O trabalho docente na educação infantil: os desafios na relação entre professor de educação física e professor de educação infantil - Recco, Kethylin Viotto [UNESP] (2014)
This study deals with teaching in Early Childhood Education, focusing on the challenges of the teaching professionalization process in the relationship among Physical Education teachers and Educationalists, drawing attention to the issue of the collaboration culture. In this context, it is possible to identify the following study problem: Which are the aspects that demonstrate a collaboration culture in the teaching professionalization process, involving the teaching work in the relationships established among the Physical Education teachers and Educationalists in the context of Early Childhood Education? We assume that teaching at school is still at the age of teaching as a vocation or at the age of teaching as a craft, in which teachers learn and develop professionally and primarily depending on the individual and collective experiences and on social relations that are established among peers. As a general goal, we seek to understand the aspects that point to a collaboration culture in the teaching professionalization process, involving the teaching work among Physical Education teachers and Educationalists. To collect the data, we chose the qualitative research using exploratory case study type and techniques such as: the questionnaire; observation; documentary sources and the semi-structured interview. Content analysis was used to treat the data. Nine teachers from three schools (A, B and C) participated in this study. In each school there was an Educationalist, a Pedagogical Coordinator and a Physical Education teacher. Among the results it was possible to observe: the contribution of academic education for teachers work in Early Childhood Education; the valorization of continued formation, individual readings and dialogue with experienced colleagues; good relationships among all teachers. In general, teaching practices developed in Physical Education and in Early Childhood Education were not related to each other; moments of planning...